The Correlation Between The Sixth Grade Students’ Metacognitive English Learning Strategies and Their Basic Grammar Mastery in SDN 4 Gelumbang: Penelitian - Setiawan, Afif; Ramadana, Restu; Firdaus, Masagus (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study investigates the correlation between sixth-grade students' metacognitive English learning strategies and their basics of grammar mastery at SDN 4 Gelumbang. The study utilized a quantitative correlational design with a sample of 33 students drawn from a population of 146 learners. Data were gathered via a metacognitive instructional strategy questionnaire and a fundamental grammar assessment. The findings indicated an average and statistically significant advantageous link between the application of metacognitive English learning strategies and students' proficiency in fundamental grammar. The findings showed that the application of metacognitive methods significantly contributes to improving student grammatical competence at the elementary level. The study advocates for English teachers to incorporate metacognitive strategy training into their strategies for teaching to enhance learner independence and enhance educational outcomes.